Parent–Child Conflict Profiles in Chinese American Immigrant Families: Links to Sociocultural Factors and School‐Age Children's Psychological Adjustment. Issue 1 (20th May 2020) - Chung, Sara; Zhou, Qing; Kho, Carmen; Main, Alexandra
Abstract : Research suggests that parent–child conflict is a salient family process in Asian immigrant families and often a stressful experience for Asian American youth due to value discrepancies between Asian and Western cultures. The present study examined ratings of parent–child conflict across conflict topics from parents' and children's perspectives in a sample of Chinese American immigrant families with school‐age children ( N = 239; age = 7.5–11 years). Latent profile analyses identified three parent‐rated conflict profiles and four child‐rated conflict profiles. Parent and child conflict profiles were unrelated to each other and differentially related to family sociocultural factors and children's psychological adjustment. Parents' moderate conflict profile scored highest on parent‐rated child behavior problems and had the highest household density and lower parent Chinese orientation. Children's moderate‐specific and high conflict profiles scored higher on child‐reported behavior problems than the low conflict profile. These results highlight the need to assess family conflict from both parents' and children's perspectives and target parent–child conflict communication as a pathway to prevent or reduce behavioral problems in Chinese American children of immigrant families. Resumen: Las investigaciones sugieren que el conflicto entre padres e hijos es un proceso familiar destacado en las familias de inmigrantes asiáticos, y generalmente una experiencia estresante para los jóvenes estadounidenses de origen asiático debido a las discrepancias de valores entre las culturas asiáticas y occidentales. El presente estudio analizó las evaluaciones del conflicto entre padres e hijos entre varios temas de conflicto desde las perspectivas de los padres y los hijos en un muestra de familias de inmigrantes sinoestadounidenses con niños en edad escolar (N = 239; edad = 7.5 a 11 años). Los análisis de perfiles latentes identificaron tres perfiles de conflicto evaluados por los padres y cuatro perfiles de conflicto evaluados por los niños. Los perfiles de conflicto de los padres y los hijos no se relacionaron entre sí, y estuvieron asociados diferencialmente con los factores socioculturales familiares y con los resultados de la adaptación de los niños. El perfil de conflicto moderado de los padres tuvo el puntaje más alto en los problemas de comportamiento de los niños evaluados por los padres, tuvo la densidad familiar más alta y una menor orientación china de los padres. Los perfiles de conflicto alto y moderado‐específico de los niños tuvieron un mayor puntaje en los problemas de comportamiento informados por los niños que el perfil de conflicto bajo. Estos resultados destacan la necesidad de evaluar el conflicto familiar tanto desde las perspectivas de los padres como desde las de los niños y se centran en la comunicación de conflictos entre padres e hijos como vía para evitar o reducir los problemas de comportamiento en los niños sinoestadounidenses de familias inmigrantes. 摘要: 研究表明，在亚洲移民家庭中，家长与子女之间的冲突是一个显著的家庭过程。由于亚洲文化和西方文化之间的价值差异，对亚裔美国青年而言，它往往是痛苦的经历。本研究考察了父母的角度和孩子的角度，他们各自就各种冲突主题中的亲子冲突给出评级。研究样本是美籍华人移民家庭学龄儿童（人数 ＝239人; 年龄= 7.5至11岁)。潜在概况分析确定了由父母评定的三个级别冲突状况和由儿童评定的四个级别的冲突概况。就家长和孩子评定的冲突概况来看，两者是互不相关的。但它们与家庭、社会文化因素和孩子心理调适结果方面的相关程度存在着差异。家长的中度冲突在家长评定的儿童问题上得分最高，往往家庭成员密度最高，父母的中国取向较低。在儿童报告的行为问题上，儿童的特定的那些中度冲突和高冲突情况与低冲突情况相比得分更高。这些结果强调了从父母和孩子两方面的角度来评估家庭冲突的必要性，并将亲子冲突沟通这种途径定为预防或减少移民家庭中的华裔美国儿童行为问题。